Land Dispute Settlement According to Local Wisdom in The Tenganan Pegringsingan Traditional Village, Bali - I Ketut Oka Setiawan (Green Publisher Indonesia, 2022)
Except for people with customary rights, not all customary law communities have the power to make, implement, and enforce existing regulations. As long as it does not conflict with national interests, the existence of this right in land law is still acknowledged. Disputes arising inside its territories are likewise not prohibited from being addressed using local customary law. Because 'custom or customary law' is one of the roots of state law. In comparison to state rules, the state strives to resolve civil issues by consensus in order to accomplish justice for all parties. The results of this study are also similar, however dissatisfied parties (citizens) are not prohibited from settling through state courts. In this case, the recognition of state law is not only positive, even the judge can cancel the claim of the plaintiff who is not willing to be resolved first through the village judge. It is just that the articles that give strict orders are rarely used in practice.